Girlfriends' get-together craft book - Ross, Kathy (Katharine Reynolds), 1948- (Ross, Kathy (Katharine Reynolds), 1948- Girl crafts., 2007)
Provides step-by-step directions for twenty-two crafts designed for those who are interested in fashion, decor, dolls, and jewelry.